Faktor Penyerangan Korea Utara terhadap Korea Selatan di Sekitar Pulau Yeonpyeong pada Tahun 1999 dan 2002 - Firdausia Zeta Abidin; Satwika Paramasatya (Journal of International Relations Diponegoro, 2019)
It is essential for every country in the world to have national interests for their own prosperity,even though at some points it may be contradicting the other countries. North Korea is one ofthe countries which national interests are contradicting with its neighbor country, SouthKorea. North Korea’s effort to achieve its national interests is also disturbing other countries’common goal, the world peace. This research aims to explain North Korea’s reason inYeonpyeong Island 1999 and 2002 attacks, through neoclassical realism theory. There are twofactors explained in the neoclassical realism theory, the external and internal factor. The resultof this research showed that the attacks happened because North Korea is weak in theinternational system and its political system is focusing on military. Those are the reasons whyNorth Korea used military forces to meet its national interests.